Multicomponent Synthesis, Characterization of Novel Pyrimidine Derivatives with Anti-cancer Potential - Devidi, Swetha; Manickam, M Swamivel; Suresh, R (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Design and development of target specific anti-cancer agents is a central research goal. Materials and Methods: Substituted pyrimidines were synthesized from substituted enamine, triethoxy methane and ammonium acetate. Characterization was done using IR, 1H-NMR, and mass spectra. Cytotoxicity was tested using MTT Assay on A 549, B16F10, SiHA, and MCF-7 cells. Results: Synthesized derivatives displayed noticeable cytotoxicity against tested cancer cell lines. Conclusion: Evaluated cell lines were susceptible to the novel pyrimidine derivatives, which may be transformed into potent anti-cancer leads.
Keywords: Multicomponent synthesis; Pyrimidines; Anti-cancer